PUBLIC AWARENESS ON HARMFUL ALGAL BLOOM (HAB) IN LAMPUNG BAY - Aditya, Vishnu; Koswara, Asep; Fitriya, Nurul; Rachman, Arief; Sidabutar, Tumpak; Thoha, Hikmah (Marine Research in Indonesia, 2013)
Harmful algal blooms (HABs) cause various problems, such as water quality degradation, fauna mass mortality and impairment of human health. Water quality monitoring in Lampung Bay has been conducted by Lampung Marine Aquaculture Office (BBL) of the Ministry of Marine Affairs and Fisheries since 1994. Occurrence of Pyrodinium bahamense var. compressum (Pbc), a causative organism of paralytic shellfish poisoning (PSP), has been recorded but threats caused by HABs have never been reported. A study aimed to know the level of public knowledge and awareness about HABs in Lampung Bay has been conducted. The components of group respondents consisted oflocal governments, academics and coastal communities. Awareness from each component was examined includinggeneral HAB knowledge, HAB impact to the community, HAB occurence and local knowledge of HAB. Data of HAB knowledge were collected through questionnaire and focus groupÂ  discussion. The result showed that 40.5% of respondents had knowledge of HABs phenomena and 51.3% respondents only know signs or indicators of HAB occurrence, while only 1.4% respondents had knowledge of local HAB occurences. The direct impact of HABs to the community was not commonly known by the respondents. Only a few cases of poisoning after eating seafood were reported. It can be concluded that there was lack of public knowledge and awareness on HABs in LampungBay. Intensive public awareness programs about HABs should be conducted in order to reduce risk towards HABs in Lampung Bay.